Workshop Berbasis Studi Kasus Meningkatan Pemahaman Dangerous Goods Handling pada Peserta Diklat di Politeknik Penerbangan Palembang - Thursina Andayani; Yeti Komalasari; Wildan Nugraha; Fauziyah Nur (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
Aviation safety requires the proper handling of dangerous goods, which encompasses core competencies in classification, identification, labeling, packaging, and handling procedures. This community service activity aims to enhance aviation trainees' understanding of dangerous goods handling principles through a case-study-based workshop conducted at Politeknik Penerbangan Palembang. The face-to-face training method included material delivery, interactive discussions, case studies, and label identification demonstrations, focusing on the nine classes of dangerous goods, packaging and labeling requirements, goods acceptance procedures, and initial emergency response steps. Observation results and group discussions showed active participant engagement, with most trainees able to identify the nine dangerous goods classes, determine appropriate hazard labels, and explain initial handling procedures for the given scenarios. This workshop is expected to strengthen safety culture and support the improvement of human resource competencies in the air transportation sector. Keywords: dangerous goods handling; aviation safety; workshop; case-based learning; aviation trainees.